Discharge instructions given to women following delivery by cesarean section in Sub-Saharan Africa: A scoping review - Juliet Musabeyezu; Jenna Santos; Anne Niyigena; Ange Uwimana; Bethany Hedt-Gauthier; Adeline A. Boatin (Public Library of Science (PLoS), 2022)
Objective A scoping review of discharge instructions for women undergoing cesarean section (c-section) in sub-Saharan Africa (SSA). Method Studies were identified from PubMed, Globus Index Medicus, NiPAD, EMBASE, and EBSCO databases. Eligible papers included research based in a SSA country, published in English or French, and containing information on discharge instructions addressing general postnatal care, wound care, planning of future births, or postpartum depression targeted for women delivering by c-section. For analysis, we used the PRISMA guidelines for scoping reviews followed by a narrative synthesis. We assessed quality of evidence using the GRADE system. Results We identified 78 eligible studies; 5 papers directly studied discharge protocols and 73 included information on discharge instructions in the context of a different study objective. 37 studies addressed wound care, with recommendations to return to a health facility for dressing changes and wound checks between 3 days to 6 weeks. 16 studies recommended antibiotic use at discharge, with 5 specifying a particular antibiotic. 19 studies provided recommendations around contraception and family planning, with 6 highlighting intrauterine device placement immediately after birth or 6-weeks postpartum and 6 studies discussing the importance of counselling services. Only 5 studies provided recommendations for the evaluation and management of postpartum depression in c-section patients; these studies screened for depression at 4-8 weeks postpartum and highlighted connections between c-section delivery and the loss of self-esteem as well as connections between emergency c-section delivery and psychiatric morbidity. Conclusion Few studies in SSA directly examine discharge protocols and instructions for women following c-section. Those available demonstrate wide variation in recommendations. Research is needed to develop structured evidence-based instructions with clear timelines for women. These instructions should account for financial burden, access to resources, and education of patients and communities.